UZBEKISTAN WITH MALAYSIA IN THEIR RELATIONSHIP CULTURAL OF COMMUNICATIONS HELD PLACE (ACTIVITIES OF "UZBEKISTAN-MALAYSIA" SOCIETY EXAMPLE) - Benazir B. Khomidova (International Scientific and Current Research Conferences, 2023)
Uzbekistan and Malaysia have a strong relationship in cultural and communication exchanges. The "Uzbekistan-Malaysia" society is an example of the activities that take place between the two countries. This society promotes cultural connections, language exchanges, and educational partnerships. It also encourages tourism and business collaborations between Uzbekistan and Malaysia. Through these activities, people from both countries can learn about each other's traditions, customs, and way of life. The society serves as a platform for mutual understanding and appreciation, promoting a positive relationship between Uzbekistan and Malaysia.